Variations in vitamin D status among Chinese children aged 1–6 years during the COVID-19 pandemic - Qiao, Yongfeng; Wang, Xiaoqin; Ma, Yanfen; Hu, Jian (Frontiers in Public Health, 2025)
BackgroundVitamin D deficiency has been a critical global health issue within the pediatric population. Closed-off management brought about by the COVID-19 pandemic has drastically impacted outdoor activities and sunlight exposure, however, whether it indirectly further exacerbated the vitamin D deficiency has not been largely investigated, especially among children in China. The purpose of this study was to evaluate 25(OH)D concentrations in children before and during the COVID-19 lockdown and to analyze the factors influencing their vitamin D status.MethodsA cross-sectional survey included children aged 1–6 years from Han Zhong Central Hospital in the southern Shanxi Province of China. This study examined healthy children from a pediatric health care department over two periods: before COVID-19 (March 2019–February 2020), and during COVID-19 (March 2020–February 2021). Total 25(OH)D concentrations were compared between the two observation periods. Vitamin D status was determined by 25(OH)D concentrations: deficient (<20 ng/ml), insufficient (20–29 ng/ml), and sufficient (30–100 ng/ml).ResultsThe study involved 6,780 children, with 52.8% being 1-year-olds, 23.1% being 2-year-olds, and 24.1% being 3 to 6-year-olds. Boys and girls were 52.8 and 47.2%, respectively. The actual prevalence of deficiency in vitamin D nutritional status among children was 2.8%, with 87.1% of cases in those aged 3 to 6 years. Vitamin D insufficiency was 18.3%, affecting 54.8% of the same demographic. The average of 25(OH)D concentration were 38.2 ± 9.8 ng/ml, significantly varying by age and season. 25(OH)D concentrations decreased with age, from 42.3 ± 8.8 ng/ml at 1-year-olds to 37.4 ± 8.2 ng/ml at 2-year-olds, and further to 30.2 ± 8.1 ng/ml at 3 to 6-year-olds. Seasonal variations showed that 25(OH)D concentrations were higher in spring (38.7 ± 10.1 ng/ml), summer (38.7 ± 10.0 ng/ml), and fall (38.6 ± 9.2 ng/ml) in comparison to winter (36.0 ± 9.8 ng/ml). Additionally, the concentrations of 25(OH)D in spring exhibited a decrease during the COVID-19 pandemic (37.9 ± 10.3 ng/ml) in comparison to the pre-pandemic measurements (39.3 ± 9.9 ng/ml) (p = 0.008), while winter concentrations increased from (35.1 ± 10.4 ng/ml) to (37.9 ± 10.3 ng/ml) during the pandemic (p = 0.002).ConclusionThe research indicated that vitamin D deficiency is uncommon among Chinese children, with 25(OH)D concentrations experiencing a notable decline in those aged 3–6 years. The findings suggested a potential need for tailored supplementation strategies and possibly higher doses for this age group, along with monitoring 25(OH)D concentrations to evaluate supplementation effectiveness. COVID-19-related restrictions minimally affected children’s 25(OH)D concentrations, revealing the nutritional implications of the pandemic.